Analisis Pemikiran Saadoe’ddin Djambek Tentang Waktu Shalat Di Daerah Abnormal (Kutub) - Muhajir, Muhajir (MADINAH, 2018)
Five-day prayer is a service that must be done in any condition and situation. Worship required by Allah SWT on the people of the Prophet Muhammad, one of which is prayer worship. The law of prayer is obligatory in the sense that is addressed to every person who is subject to the burden of law (mukallaf) and does not escape the obligation of someone to pray except if he has done it himself according to his provisions and cannot be represented, because what God wants in that action itself as a sign of obedience to God. Prayer is an obligation for Muslims, therefore we must know when the time of entry and passing of prayer times must be known carefully and well, not until the time of entering prayer has done it, consequently the prayer will be in vain without merit can even be done illegally. Because one of the requirements for the validity of prayer is to perform the prayer at the appointed time. Saadoe'ddin Djambek is one of the birth experts born in Bukittinggi (29 Rabi'ul Awal 1329 H or March 24, 1911 AD). An expert on rukyat reckoning, commonly called Datuk Sampono Radjo, is the son of a great ulama from Minangkabau, namely Sheikh Muhammad Djamil Djambek. Saadoe'ddin was born from a large family of Djambek who were educated, Islamic, respected and respected by the wider community of his day. The thought of Saadoe'ddin Djambek is a combination of reckoning experts and astronomers. In addition, his thoughts also tended to attempt to integrate the interpretations of scholars with astronomical theories in understanding passages relating to the initial provisions of prayer times. If most experts equate the prayer time with the extreme climate with the closest area that isstill identified during prayer times, Saadoe'ddin still adheres to the fact that the prayer times of an area cannot follow other regions because of differentlatitude. Judging from jurisprudence, pengqiyasan Saadoe'ddin Djambek above did not find a specific prayer time with the condition that people fall asleep or fainted was not right, because in reality they were in a state of being aware and aware of the natural state of their area. The author in this case tends to the opinion of T. Djamaluddin, that in fact for certain unidentified prayer time schedules, better and more certain use local normal time, before and after extreme time using the clock, so that the rhythm of prayer times will be regular and not difficult because it does not intersect with real phenomena in the area. The prayer time schedule also uses local latitude data and local time.